The Effect of the Interest Rate on a Credit System - Amaral, Amaury S.; Crepaldi, Antônio F. [UNESP]; Bautista, Carlos [UNESP]; Silva, Geraldo E.; Ferreira, Fernando F. (Springer Nature, 2024)
The present paper adopts a novel approach grounded in a recent multi-agent economic model to explore the propagation of an interest policy rate, which serves as the cornerstone of the banking system. Starting from previous well-known agent-based models, we introduce two subsidiary mechanisms to enhance the analytical framework. The first mechanism revolves around price formation, leveraging localized consumption demand and inventory dynamics. The second mechanism incorporates an agent matching process based on the lowest price mechanism. Additionally, we establish a consumer network wherein credit flows for both consumption and production traverse an interconnected banking system governed by a central bank acting as the monetary authority. Consequently, interest rates and interest policy rates undergo fluctuations stemming from the spread of endogenous systemic risks across economic activities. These fluctuations exert influence on critical macroeconomic aggregates, including employment levels, demand patterns, price dynamics, net worth, and credit variables. The central finding of our study revolves around the occurrence of a stagflationary process devoid of anticipatory expectations. Moreover, this outcome is closely linked to the existence of an interest rate ratchet effect originating from a corresponding leverage ratchet effect. As a result, numerous small banks experience failure, primarily due to the perceived increase in uncertainty within the banking network. The system becomes shockingly vulnerable, ultimately succumbing to bankruptcy. In an increasingly competitive environment, additional factors such as consumption patterns, agents’ income losses, and other macroeconomic aggregates further contribute to the propagation of uncertainties within the system. Consequently, an unexpected interest rate ratchet effect takes hold, deepening the intricacies of the overall dynamics, evidenced by correlations based on official statistics.
Keywords: Agent-based model; Credit; Network; Price formation